Supervision Function of the Regional House of Representatives Against the Handling of the COVID-19 Pandemic - Octavia Putri Pangestu; Asep Nurjaman; Muhammad Kamil (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
This research aims to look at the supervision carried out by the Malang City DPRD in the handling of the COVID-19 pandemic in the Malang City Government. DPRD supervision is carried out to ensure the implementation of the policies and plans that have been set, and the objectives of handling COVID-19 can be achieved effectively and efficiently. The use of surveillance theory became particularly appropriate in this study. This research method uses qualitative descriptive methods. The data sources obtained are primary data and secondary data. Primary data is obtained from interview results, while secondary data is obtained from literature studies, laws, and other important documents. This research concluded that supervision by the DPRD is needed to control the performance of local governments in handling COVID-19, especially when the handling of COVID-19 is not yet maximal. The views and recommendations of the DPRD are needed to be in harmony with the expectations of people who want the pandemic problem to be quickly resolved.